OPTIMALISASI SKILL OLAHRAGA DAN SENI PESERTA DIDIK MELALUI PENGELOLAAN SARANA PRASARANA PEMBELAJARAN - Defri Cahyadi; Yetri Hasan; Erni Yusnita (STKIP Pesisir Selatan, 2026)
This study aims to analyze the optimization of students' sports and arts skills through the management of learning facilities and infrastructure at SMA Negeri 1 Bangkunat Belimbing. The focus of the study is on the planning, utilization, and control of facilities and infrastructure in supporting the improvement of students' skills, participation, and self-confidence. This study uses a descriptive qualitative approach. Data collection techniques include observation, in-depth interviews, and documentation with informants consisting of the principal, vice principal in charge of student affairs, as well as sports and arts teachers. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the optimization of sports and arts skills is achieved through the planning of facilities and infrastructure that is carried out in stages and based on the real needs of students. The use of facilities is carried out in a scheduled and controlled manner in both learning and extracurricular activities. This management has a positive impact on increasing student enthusiasm, active participation, and self-confidence, as well as significantly improving technical sports and arts skills. This research emphasizes the specific management of facilities and infrastructure as a strategy for improving students' sports and arts skills, which has been rarely discussed in previous educational management studies.